Diagnostika a další péče o pacienty s tyreoidálními uzly: doporučení American Thyroid Association 2015 modifikované pro podmínky České republiky - Jiskra, Jan (Casopis lekaru ceskych, 2017)
Thyroid nodules are common finding. Most of them are of benign origin without thyroid dysfunction. Diagnosis is based on evaluation of thyroid function by assessment of serum thyroid stimulating hormone, and ultrasound for the purpose to identify the nodules which should be referred to fine needle aspiration biopsy (FNAB). The nodule size, ultrasound pattern and clinical risk factors should be considered before the FNAB is performed. The FNAB results should be categorized based on the risk of malignancy to improving a standardization of the patients management and minimizing number of false negative and false positive FNAB results. The most appropriate categorizing system seems to be Bethesda classification, although it is not completely optimal mainly because of controversial Bethesda III category.
Keywords: Spojené státy americké; Thyroid Neoplasms; směrnice pro lékařskou praxi jako téma; Česká republika; nádory štítné žlázy; United States; fine needle aspiration biopsy Bethesda classification.; ultrasound; lidé; Practice Guidelines as Topic; thyroid nodule; retrospektivní studie; Retrospective Studies; thyroid cancer; uzly štítné žlázy; Humans; Thyroid Nodule; Czech Republic